The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5603/gp.a2017.0013
|View full text |Cite
|
Sign up to set email alerts
|

Complete response to acupuncture therapy in female patients with refractory interstitial cystitis/bladder pain syndrome

Abstract: Objectives: Interstitial Cystitis/Bladder Pain syndrome (IC/BPS) is a considerable issue in urology and gynecology and unfortunately, the treatment options recommended are not fully efficient. Therefore, in this study we aimed to determine the effectiveness of acupuncture treatment in patients with refractory IC/BPS. Results: There was a statistically significant decrease in all of the scores evaluated at first month compared with the baseline. While the change in VAS score in 1, 3, 6 and 12 th months were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
6
0
10
Order By: Relevance
“…É comprovado que a Acupuntura é o método de tratamento de dor mais procurado nos quadros de dor lombar. Tem resultados positivos nos tratamentos de dor quando comparado ao grupo controle (Sham Acupuncture) em diferentes etiologias de modo geral (Zucker et al, 2017;Lam et al, 2017;Sönmez & Kozanhan, 2017;Mist & Jones, 2018;Genovese & Mao, 2019;Valente et al, 2020).…”
Section: Discussionunclassified
“…É comprovado que a Acupuntura é o método de tratamento de dor mais procurado nos quadros de dor lombar. Tem resultados positivos nos tratamentos de dor quando comparado ao grupo controle (Sham Acupuncture) em diferentes etiologias de modo geral (Zucker et al, 2017;Lam et al, 2017;Sönmez & Kozanhan, 2017;Mist & Jones, 2018;Genovese & Mao, 2019;Valente et al, 2020).…”
Section: Discussionunclassified
“…[ 23 , 24 ] A previous study has also reported that acupuncture is an effective treatment method in IC/BPS patients. [ 17 ] Therefore, we assumed that the positive effects of CHM and acupuncture might alleviate the psychological burden of patients with IC/BPS and subsequently decrease the risk of mental disorders. However, there was no statistically significant difference in the risk of mental disorders between IC/BPS patients with and without CHM granules or acupuncture treatment (adjusted HR: 0.99, 95% CI: 0.58–1.68).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Acupuncture demonstrated positive effect on bladder volume, suppressed bladder contraction, and changed the firing properties of the micturition center. [ 17 , 18 ] Despite these positive effects on urinary symptoms, clinical research regarding the effects of TCM on IC/BPS is scarce. Previous case series were often limited by ambiguous enrollment criteria and short follow-up duration.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to physical therapy, because of safety and relatively affordability, acupuncture can be considered an option in women affected by IC/BPS based on studies suggesting the effectiveness of the technique, although the evidence is limited and more data are required [11,29,[33][34][35].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%